Printed circuit board assembly and a method for manufacturing the printed circuit board assembly - YABRE GNITABOURE; STRICOT YVES (2015)
Printed circuit board assembly including an optical subassembly having a carrying face for carrying at least one optoelectronic component in a such way that light emitted from/directed to is transmitted through the optical subassembly; a printed circuit board having a supporting area for supporting the optical subassembly; wherein the printed circuit board supporting area includes a hole lodging at least one part of the optoelectronic component and wherein at least one part of the carrying face is fixed by flip-chip bonding to at least one part of the supporting area.